The relationship of organisational commitment and turnover intention amongst tourism employees in Kota Kinabalu, Sabah: the moderating effect the job tenure - Norzaris Abdul (2014)
The purpose of this study is to examine the relationship between components of organisational commitment (affective, continuance and normative) towards turnover intention amongst tourism employees and the effect of job tenure as mediator, specifically those employed by tour operators in Kota Kinabalu. A total of 110 tour operator employees completed the questionnaire. A self-administrated was used by the researchers to collect data. The results indicate that affective commitment and normative commitment were negatively related to turnover intention. While continuance commitment were not negatively related to turnover intention. This study found out job tenure did not moderate the relationship between organization commitment and turnover intention. Findings could highlight the importance of tour operator creating strong relationships with employees, and not just tourists